Semi-flexible Bionic Whisker Sensor Based on Triboelectric Nanogenerators - Wang, Xinyu; Xu, Peng; Liu, Jianhua; Wang, Siyuan; Chen, Tianyu; Guan, Tangzhen; Tao, Jin; Xu, Minyi (2021 International Conference on Artificial Intelligence and Electromechanical Automation (AIEA), 2021)
Tactile sensing can provide sufficient cues concerning the geometry and texture of the contact in unknown environments. This paper proposes a semi-flexible triboelectric bionic whisker sensor (TBWS) as a novel scheme for robotic tactile perception. To be specific, it comprises power generation units (38mm in length, 18mm in width, and 10mm in thickness), octagonal plate, carbon fiber shaft (300mm in length, 1.5mm in diameter), shape memory alloy, and supporting parts. The octagonal plate hit the power generation units resulted from the carbon fiber shaft subjected to the external force, allowing to gene rate signals from the principle of via triboelectric and electrostatic induction. One another feature of the proposed sensors is that it is inspired by the structure of rat whisker follicles characterized by complex higher-order dynamics. Experimental result shows that TBWS can help robots accomplish autonomous work in complex environments. There is no doubt that the invention of sensor TBWS provides a new direction for robots' future research.